Enhanced Proliferation of Porcine Bone Marrow Mesenchymal Stem Cells Induced by Extracellular Calcium is Associated with the Activation of the Calcium-Sensing Receptor and ERK Signaling Pathway - Jingjing Ye; Wei Ai; Fenglin Zhang; Xiaotong Zhu; Gang Shu; Lina Wang; Ping Gao; Qianyun Xi; YongLiang Zhang; Qingyan Jiang; Songbo Wang (Stem Cells International)
Porcine bone marrow mesenchymal stem cells (pBMSCs) have the potential for application in regenerative medicine. This study aims to investigate the effects of extracellular calcium (Ca2+o) on pBMSCs proliferation and to explore the possible underlying mechanisms. The results demonstrated that 4 mM Ca2+o significantly promoted pBMSCs proliferation by reducing the G0/G1 phase cell percentage and by increasing the S phase cell proportion and the proliferation index of pBMSCs. Accordingly, Ca2+o stimulated the expression levels of proliferative genes such as cyclin A2, cyclin D1/3, cyclin E2, and PCNA and inhibited the expression of p21. In addition, Ca2+o resulted in a significant elevation of intracellular calcium and an increased ratio of p-ERK/ERK. However, inhibition of calcium-sensing receptor (CaSR) by its antagonist NPS2143 abolished the aforementioned effects of Ca2+o. Moreover, Ca2+o-induced promotion of pBMSCs proliferation, the changes of proliferative genes expression levels, and the activation of ERK1/2 signaling pathway were effectively blocked by U0126, a selective ERK kinase inhibitor. In conclusion, our findings provided evidence that the enhanced pBMSCs proliferation in response to Ca2+o was associated with the activation of CaSR and ERK1/2 signaling pathway, which may be useful for the application of pBMSCs in future clinical studies aimed at tissue regeneration and repair.